Novel oxazolidinone calcitonin gene-related peptide (CGRP) receptor antagonists for the acute treatment of migraine. Issue 21 (1st November 2015) - Crowley, Brendan M.; Stump, Craig A.; Nguyen, Diem N.; Potteiger, Craig M.; McWherter, Melody A.; Paone, Daniel V.; Quigley, Amy G.; Bruno, Joseph G.; Cui, Dan; Culberson, J. Christopher; Danziger, Andrew; Fandozzi, Christine; et al.
Graphical abstract